PENGARUH ETOS KERJA ISLAMI TERHADAP KINERJA KARYAWAN PADA KOPERASI AGRO NIAGA INDONESIA (KANINDO) SYARIAH JAWA TIMUR - Alfa Shafissalam; Misbahuddin Azzuhri (Jurnal Ilmiah Mahasiswa FEB, 2013)
Aim of this study is to analyze impact of Islamic ethics to performance of employee. Research question of this study can determines as “Is there any significant impact both simultaneously and partially on Islamic ethics to performance of employee?” Hypotheses of this study is “Islamic ethics has significant impact to performance of employee.” The research is conduct in Kanindo Syariah East Java, then, as much as 36 as respondents of this research. Data is collected by questionnaire and documenter. Data is analyzed by doubled regression analysis. The finding of the analysis show that Islamic ethics does not significantly affect to the performance of employee. Indeed, among variable work based on aqeedah, work based on learned, work based on God rules and work following His right path, just work following His right path as partial affect significantly to performance of employee. Implication of this study to Kanindo Syariah East Java is giving suggestion to personalia affairs in order to increasing performance quality of the employee by increasing Islamic ethics through empirical understanding.   Key words: Islamic Ethics, Empirical Understanding, Performance of Employee